Distinct Aspects of Income and Expenses in the Context of Loneliness: Example of the Republic of Moldova - Țurcanu, Olesea (Acta Universitatis Danubius. Œconomica, 2025)
This article analyses single-person households in comparison with other types of households in terms of sources of income and distribution of expenditure. The research was conducted based on documentation and secondary observation, using descriptive and comparative analysis methods, as well as quantitative analysis techniques and statistical processing of indicators related to household income and expenditure in the Republic of Moldova. Most single-person households are made up of employed people and pensioners. They have higher monthly incomes than the national average, but also higher than average expenditure. At the same time, the disposable income of these households showed an upward trend in the period 2019–2023, allowing them to cover their expenses in full. The originality of the study lies in highlighting an often-neglected economic category – households of people living alone – and in offering a different perspective on their sources of disposable income and consumption expenditure in the Republic of Moldova, highlighting the differences compared to other family households.